Why natural language processing for dementia detection is not reaching the NHS frontline - Ellie Maria Koseda (British Journal of Healthcare Management, 2026)
Natural language processing could help to tackle delayed diagnosis in dementia care, allowing more patients to access services during the ‘intervention window’, but implementation has been slow. Ellie Koseda explores barriers to adoption of this technology and other AI-based tools, including fragmented care pathways, limited interoperability and ongoing governance concerns.